Healing rites of passage - Kearney, Peter James, author.
1 online resource.
Keywords: This book examines how 'Therapeutic Recreation' transforms the social health of children enduring or recovering from life-threatening illnesses such as cancer and leukaemia. With studies drawn from 'Serious Fun' projects in the USA, the UK, France, Ireland and Israel, the author explores how camp experiences in convivial circumstances help to bring about healing. Employing central concepts from sociology and anthropology, such as 'liminality', 'mimesis' and 'salutogenesis', Healing Rites of Passage explains why a brief secluded holiday can reform the campers' shared situation of life-threatening illnesses towards health and flourishing. The whole process can be understood in terms of a 'rite of passage', as structured camp experiences enable children to shed previous 'sick roles' and pass through a series of challenges in order to achieve social re-integration with a renewed zest for living. An empirically grounded study that reveals the analytic value of master concepts in the social sciences, this book will appeal to scholars in the fields of sociology, anthropology, paediatrics, social theory and the sociology of health, illness and medicine.